Організаційно-економічне забезпечення технічного переоснащення виробництва підприємств машинобудування - Безугла, Дар'я Валеріївна (НТУ "ХПІ", 2018)
Дисертація на здобуття наукового ступеня кандидата економічних наук за спеціальністю 08.00.04 – економіка та управління підприємствами (за видами економічної діяльності). – Національний технічний університет "Харківський політехнічний інститут", Харків, 2018. Дисертація присвячена дослідженню і обґрунтуванню теоретичних підходів щодо розвитку організаційно-економічного забезпечення технічного переоснащення виробництва (ТПВ) підприємств машинобудування, а також розробці науково-методичних напрямків його удосконалення. В роботі уточнено визначення сутності ТПВ як багатоаспектного організаційно-економічного процесу; розроблено модель ТПВ, що визначає етапність і системну результативність його реалізації. Набула подальшого розвитку типологія планів ТПВ, що враховує техніко-технологічні особливості, а також стратегії виробничої діяльності підприємств машинобудування. Удосконалено методичний підхід щодо заміни устаткування в процесі ТПВ за критерієм забезпечення прибутку. Набули подальшого розвитку методичні підходи щодо забезпечення організаційно-економічної гнучкості підприємства в процесі ТПВ. Запропоновано методичний підхід щодо розробки і виконання інвестиційного проекту ТПВ. Теоретично обґрунтовано та розроблено організаційно-економічну структуру управління інноваційним та науково-технічним забезпеченням технічного переоснащення виробництва підприємств машинобудування. Запропоновано методичний підхід щодо обґрунтування актуальних напрямів ТПВ на основі розробленої моделі "Формування організаційно-економічних переваг" підприємства.

Thesis for granting the Degree of Candidate of Economic Sciences (PhD) speciality 08.00.04 – Economics and management of enterprises (by types of economic activity) – (08 – Economics). – National Technical University "Kharkiv Polytechnical Institute", Kharkiv, 2018. The dissertation is devoted to investigation and groundation of theoretical approaches to development the organization–economic support of production technical reequipment (PTR) of machine – building enterprises, so as to elaboration the scientific – methodical directions for it perfection. It is defined more precisely the essens of production technical reequipment being the multi-aspects organization–economic process. It is worked out the organization–economic PTR – model that determins stages and system resultivity of it realization. It is elaborated the typology of PTR, that contains 12 types of plans and the system of indexes for it realization, being approached to innovative and production strategies of enterprises. It is improved the methodic of equipment substitution at PTR-process according to profitability criterion. It is executed the further development of methodic principles of providing the organization-economic flexibility of an enterprise at PTR-process, based at elaborated system of indexes, that characterize expenditure of financial and time resources of an enterprise. It is offered to analyze cycles of flexible innovative development of an enterprise. It is improved the methodic approach to involve and effective use of investments for the aims of PTR – projects realization, based at graphic – analytical model of economic interaction "enterprise – investor". This approach embraces the stages of substantiation the most economic-effective subject of technical reequipment and coordination with investor the conditions to accomplish of PTR-project. It is executed the further development of the organization – economic structure for innovation and scientific-technical support of machine-building enterprises reequipment. It forsees creation the matrix-project structures and the program-intentioned groups at the enterprise to realize PTR-projects by the principle "researches – elaborations – industry inculcation". It is improved the methodic approach to groundation of actual PTR-directions of machine-building enterprises. It is based on developed model "Forming of organization – economic preferentials of an enterprise", which forsees comparative analysis of organization – economic potential of an enterprise and it firm-competitor at their inner scope.
Organization-economic providing the technical reequipment of production of machine-building enterprises
Keywords: основні виробничі засоби; технічне переоснащення виробництва; інновації; інвестиції; конкурентоздатність; дисертації; basic production assets; technical industry reequipment; innovations; investments; competitivness; 338.45:658.27